Oncological Safety and Outcomes of Nipple-Sparing Mastectomy With Breast Reconstruction: A Single-Centered Experience in Taiwan. (May 2015) - Ou, Kuang-Wen; Yu, Jyh-Cherng; Ho, Meng-Hsing; Chiu, Wen-Kuan; Ou, Kuang-Lin; Chen, Tim-Mo; Chen, Shyi-Gen
Abstract : Introduction: Nipple-sparing mastectomy has become a contemporary surgical treatment that achieves improved cosmetic outcomes for patients with breast cancer in Western countries. We examined oncological and cosmetic outcomes in Asian women who underwent nipple-sparing mastectomy in Taiwan. Methods: Between 2006 and 2011, 42 patients with breast cancer who underwent 44 nipple-sparing mastectomy operations with immediate reconstruction at the Tri-Service General Hospital were reviewed. The cancer type, tumor stage, reconstruction method, presence of local recurrence, presence of distant metastasis, mortality, and complications were assessed and documented. Questionnaires were used to assess and rate patients' satisfaction with regard to appearance, sensation, symmetry, color, arousal, and texture. Results: The mean follow-up period was 40.9 months (median, 45.5 months; range, 13–72 months). Among the 42 cases, only one case (2.4%) of local recurrence was observed and treated by nipple-areola complex resection. The overall complication rate was 25%, with nipple necrosis comprising 13.6%. Conclusion: Nipple-sparing mastectomy is a safe procedure in properly selected patients with breast cancer. This procedure yields similar oncological safety and cosmetic outcomes among Asians and women from Western countries.